A study on the status of hospital libraries in the First, Second, and Fourth Districts of the National Capital Region - Deuda, Von Levi E.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
There are numerous status determination studies on libraries but mostly are on public and academic libraries. There are fewer on special libraries, specially hospital libraries. This is despite the fact that hospital libraries are proven to contribute significantly to the success of hospitals. In the Philippines, there exists a gap in literature on the status of hospital libraries as the most recent one was done over two decades ago. The study determined the status of hospital libraries in the first, second, and fourth districts of the National Capital Region based on the Standard for Special Libraries in the Philippines which consists of six parts: Administration, Human Resources, Collection Development, Services, Physical Facilities, Financial Resources. Data were gathered through survey and phone calls. The results showed that most problem faced by hospital libraries can be attributed to understaffing and insufficient financial resources. This suggested that the library managers need to exert more effort to enlighten their parent institutions about the value of hospital libraries in order to receive more support, otherwise find other ways to acquire more funds for the libraries.
Thesis
Keywords: Hospital libraries -- Philippines -- National Capital Region; Medical libraries -- Philippines -- National Capital Region; Hospital libraries -- Administration -- Philippines -- National Capital Region